Teacher advocacy for the enhancement of professional learning and development in continuous professional teacher development programmes - Dasoo, N.; Muller, L. van der Merwe (South African Journal of Higher Education, 2020)
This article focuses on the key role of teachers in the decision-making process concerning the design and implementation of Continuous Professional Teacher Development (CPTD) at a network of independent schools in Johannesburg. The procedure of examining the role-players in the CPTD process and the level of ownership that teachers appropriate in setting and developing their own topics and goals for training, learning and development are discussed. Activity theory and the theory of communities of practice informed the qualitative study undertaken at three independent primary schools in geographically different areas of Johannesburg. The aim of the study was to indicate that teachers as adult learners can generate useful ideas and topics for CPTD and can inform and improve their practice by recommending effective CPTD activities. Semi-structured interviews, questionnaires and document analysis were employed as data gathering techniques to collect rich data from a purposefully selected sample of primary school teachers. Teachers described activities and methods of learning that could improve their CPTD practices. The findings identify important elements that can be applied in CPTD and professional learning contexts. The proposed elements can be implemented to enhance teacher participation, decision-making and ownership of CPTD and teacher learning.